The genetic basis for aortic aneurysmal disease. Issue 12 (19th May 2014) - Saratzis, Athanasios; Bown, Matthew J
Abstract : Aortic aneurysms are an important cause of cardiovascular death in elderly patients. At present, little is known of the pathobiology of aneurysmal disease and this limits the ability to develop non-surgical treatments to stabilise aneurysms. Both thoracic and abdominal aortic aneurysms (AAA) demonstrate a strong genetic component in their aetiology. Determination of the genetic variants associated with aneurysmal disease is one approach to increasing the understanding the pathways leading to aneurysmal degeneration of the aorta. In this review, we aim to summarise the current knowledge of the genetics underlying the two most common disease phenotypes, thoracic aortic aneurysm (TAA) and AAA. Genetically, AAA represent a multifactorial disease, with the likelihood that there are multiple variants of very low effect sizes contributing to the overall genetic disease risk. Non-syndromic TAA appears to be associated with a smaller number of risk loci with higher individual effect sizes at these loci. Candidate gene and genome-wide approaches have identified robust associations between AAA and variants in/nearby the SORT1, low-density lipoprotein receptor, DAB2IP, LRP1, ELN, CRP, TGFB and various matrix metallo-proteinase genes suggesting that aberrations of lipid metabolism and proteolytic pathways are the key contributors to disease. Some of these associations (eg, LRP1) are not associated with atherosclerosis, suggesting pathways unique to AAA. Genetic variants associated with non-syndromic TAA (ACTA2 and MYH11) are related to the TGFβ pathway, strongly implicated in syndromic TAA, thus suggesting a common pathway between syndromic and non-syndromic TAA.